Consumer Reactions to Inflation - Mueller, Eva (Quarterly Journal of Economics, 1959)
Introduction, 246. — Inflationary stimuli and consumer perceptions regarding price trends, 248. — Attitudes towards inflation, 251. — Impact on investment choices, 256. — Impact on consumer spending, 257. — Conclusions, 261.